A look at latin american cultural and creative industries' diffusion and competitiveness strategies - Redondo Méndez, Andrea Carolina (2021)
The aim of the research is to identify the strategies that have used the cultural and creative industries of Latin America for the generation of competitiveness and the processes of diffusion of their goods and services, through a nonexperimental research design that showed the situation of the Latin American cultural sector with qualitative methodology of direct approach with 50 entrepreneurs from the Latin American creative and cultural sector through in-depth interviews; as the main finding was found that the most used strategy, given its presence in the market and for the improvement of competitiveness within the cultural sector, has been cultural networking, since it has allowed them to recognize and feedback from those with the most experience in the sector, as well as the ability to identify scenarios for action and weave human networks of collaboration and knowledge. However, and in conclusion, this strategy has not represented, for the sector, the expected results, being of an autonomous type and not a structure established from state or organizational standards that support the cultural sector in each of its countries, without the State’s support and its recognition as representative industries in the region are lacking.